Solid electrolyte powder as well as preparation method and application thereof
By preparing nano-level solid electrolyte powder, the problems of high energy consumption and high production cost when coating electrode materials in the prior art are solved, and an efficient and low-cost solid electrolyte coating process is achieved.
Patent Information
- Application Number
- CN202311255372.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
The nanosolid electrolyte slurry used in existing lithium-ion batteries requires drying a large amount of solvent when covering the electrode material, resulting in high energy consumption, high production costs, and the nanosolid electrolyte particles are easily stored in layers.
A solid electrolyte powder is provided, including nano-level solid electrolyte particles, prepared by a specific preparation method, including mixing solid electrolyte coarse powder, surfactant and solvent, performing wet grinding, first heat treatment, drying and pulverizing, to obtain a solid electrolyte powder with uniform particle size and good dispersion.
This method does not require drying a large amount of solvent, simplifies the process, reduces production costs, and the solid electrolyte powder is stable during storage, making it suitable for industrial preparation.
Smart Images

Figure CN119725695A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of solid electrolyte technology, and in particular to a solid electrolyte powder and a preparation method and application thereof. Background Art
[0002] In recent years, with the promotion and application of lithium-ion batteries in consumer electronics, electric vehicles, large-scale energy storage and other fields, the demand for battery energy density has become increasingly higher. Currently, commercial lithium-ion batteries generally use organic electrolytes. There are a large number of volatile, flammable and explosive organic solvents in the battery system, and the safety issues of batteries are becoming increasingly prominent. Compared with liquid electrolytes, inorganic solid electrolytes have obvious advantages in safety and thermal stability. Therefore, all-solid-state lithium-ion batteries using inorganic solid electrolytes are considered to be the preferred solution to solve the safety problems of existing lithium-ion batteries.
[0003] Surface coating of electrode materials is one of the main uses of solid electrolytes. The solid electrolyte material used for coating electrode materials needs to have a nanometer size. At present, the solid electrolyte used for coating electrode materials is mainly nano solid electrolyte slurry. The specific process is to first mix the electrode material to be coated, the nano solid electrolyte slurry and the solvent, so that the electrode material and the nano solid electrolyte are fully mixed and evenly mixed, and then dried, and finally the nano solid electrolyte coated electrode material is obtained after heat treatment. This approach requires drying a large amount of solvent, which inevitably produces a large energy consumption. In addition, the transportation and storage cost of the nano solid electrolyte slurry is high, and it is also easy to stratify during long-term storage. The above reasons lead to the high production cost of the current solid electrolyte coated electrode materials.
[0004] Therefore, developing a nano solid electrolyte material that can efficiently and cost-effectively coat electrode materials is a technical challenge in the field of lithium-ion batteries. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present application is to provide a solid electrolyte powder and a preparation method and application thereof, which can be used for coating electrode materials efficiently and at low cost.
[0006] In order to achieve one, part or all of the above purposes or other purposes, this application adopts the following technical solutions:
[0007] In a first aspect, the present application provides a solid electrolyte powder, wherein the solid electrolyte powder comprises solid electrolyte particles, and the material of the solid electrolyte powder comprises a NASICON type phosphate solid electrolyte (Li 1+x Al x Ti 2-x (PO4)3, where 0≤x≤1) and its doped derivatives, garnet-type lithium lanthanum zirconium oxide solid electrolyte (Li7La3Zr2O12 ) and its doped derivatives and perovskite-type lithium lanthanum titanium oxide solid electrolyte (Li 3y La 2 / 3-y TiO3, wherein 0≤y≤2 / 3) and at least one of its doped derivatives, the particle size D of the solid electrolyte particles 50 Less than or equal to 500nm, D 90 / D 50 ≤3.0, the specific surface area of the solid electrolyte particles is greater than 20m 2 / g.
[0008] The solid electrolyte provided in the present application is a powder material, including solid electrolyte particles with a particle size of nanometers. Preferably, the solid electrolyte powder of the present application is composed of nanometer-scale solid electrolyte particles. The particle size D of the solid electrolyte particles is 50 Less than or equal to 500 nm, for example, it can be 20 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 400 nm or 500 nm, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. D of solid electrolyte particles 90 / D 50 ≤3.0, illustratively, it can be 1.5, 2.0, 2.5 or 3.0, etc., but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. The particle size distribution of the solid electrolyte powder can be obtained by testing with a laser particle size distribution instrument. It can be seen that the content of large-size solid electrolyte particles in the present application is low, which is conducive to direct coating of electrode materials.
[0009] Among them, in the doped derivatives of NASICON-type phosphate solid electrolytes, the doped elements are selected from at least one of B, Si, Co, and Ni; in the doped derivatives of garnet-type lithium lanthanum zirconium oxide solid electrolytes, the doped elements are selected from at least one of W, Ta, Te, and Nb; in the doped derivatives of perovskite-type lithium lanthanum titanium oxide solid electrolytes, the doped elements are selected from at least one of Mg, Sr, W, and Nb.
[0010] The specific surface area of the solid electrolyte particles of the present application is greater than 20 m 2 / g, for example, may be 22m 2 / g, 30m 2 / g, 40m 2 / g, 50m 2 / g, 60m 2 / g, 70m 2 / g, 80m 2 / g, 90m 2 / g or 100m 2 / g, etc., but are not limited to the listed values, and other values not listed in the numerical range are also applicable. The specific surface area of the solid electrolyte particles is tested by the N2 gas adsorption BET method. In the powder state, the specific surface area of the solid electrolyte particles of the present application is higher than 20m 2 / g, it can be seen that the degree of agglomeration is low and the dispersibility is good. Although there is a slurry containing nano-scale solid electrolyte particles in the prior art, if the solid electrolyte slurry is directly dried to prepare solid electrolyte powder, the solid electrolyte particles will be severely agglomerated to form agglomerates of particles with larger particle sizes or even micron-scale (the specific surface area of such agglomerated particles is usually less than 20m 2 / g), and the particle sizes of the agglomerated particles are different and cannot exist in the form of uniformly dispersed particles at the nanometer level.
[0011] The solid electrolyte powder of the present application can be stored stably, wherein the solid electrolyte particles are nano-sized, and have uniform particle size, good dispersibility, and low degree of agglomeration. When used, the solid electrolyte powder can be directly coated on the surface of the electrode material by a dry method, without the need to dry a large amount of solvent. The process is simple, and the production cost of the solid electrolyte-coated electrode material is greatly reduced.
[0012] Furthermore, the particle size D of the solid electrolyte particles 50 The solid electrolyte particle D 90 / D 10 ≤5, such as 2.5, 3, 3.5, 4, 4.5 or 5, but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The specific surface area of the solid electrolyte particles is 22m 2 / g~100m 2 / g, for example, may be 22m 2 / g, 30m 2 / g, 40m 2 / g, 50m 2 / g, 60m 2 / g, 70m 2 / g, 80m 2 / g, 90m 2 / g or 100m 2 / g, etc., but are not limited to the listed values, and other values not listed in the numerical range are also applicable. The solid electrolyte particles of the present application have high particle size concentration and good uniformity.
[0013] Furthermore, the particle size D of the solid electrolyte particles 50 The solid electrolyte particles have a diameter of 100 nm to 300 nm, such as 100 nm, 150 nm, 200 nm, 250 nm or 300 nm, but are not limited to the listed values. Other values not listed in the numerical range are also applicable. 90 / D 50 ≤3.0, such as 1.5, 2.0, 2.5 or 3.0, but not limited to the listed values, other values not listed in the numerical range are also applicable; 2.5≤D 90 / D 10 ≤5, such as 2.5, 3, 3.5, 4, 4.5 or 5, but not limited to the listed values, other values not listed in the numerical range are also applicable; the specific surface area of the solid electrolyte particles is 22m 2 / g~60m 2 / g, for example 22m 2 / g, 30m 2 / g, 40m 2 / g, 50m 2 / g or 60m 2 / g, etc., but are not limited to the listed values, and other values not listed in the numerical range are also applicable. The solid electrolyte powder within the above numerical range has high particle size concentration, good uniformity, good powder fluidity, and is easy to prepare industrially.
[0014] Furthermore, the tap density of the solid electrolyte powder is 0.05 g / cm 3 ~0.4g / cm 3 , for example 0.05g / cm 3 , 0.1g / cm 3 , 0.15g / cm 3 , 0.2g / cm 3 , 0.25g / cm 3 , 0.3g / cm 3 , 0.35g / cm 3 or 0.4g / cm 3 etc., but are not limited to the listed values, and other values not listed in the numerical range are also applicable. Preferably, the tap density of the solid electrolyte powder is 0.1 g / cm 3 ~0.4g / cm 3 The tap density can be measured by a powder tap density meter. The tap density of solid electrolyte particles in the prior art is usually greater than 0.6 g / cm 3 , while the tap density of the solid electrolyte powder of the present application is relatively small, indicating that the solid electrolyte particles have good uniformity and few agglomerated particles.
[0015] In a second aspect, the present application provides a method for preparing the above-mentioned solid electrolyte powder, the method comprising the following steps:
[0016] The solid electrolyte coarse powder, surfactant and solvent are mixed to prepare a mixed slurry, wherein the material of the solid electrolyte coarse powder includes NASICON type phosphate solid electrolyte (Li 1+x Al x Ti 2-x (PO4)3, where 0≤x≤1) and its doped derivatives, garnet-type lithium lanthanum zirconium oxide solid electrolyte (Li7La3Zr2O 12 ) and its doped derivatives and perovskite-type lithium lanthanum titanium oxide solid electrolyte (Li 3y La 2 / 3-y TiO3, wherein 0≤y≤2 / 3) and at least one of its doped derivatives, the mass ratio of the surfactant to the coarse solid electrolyte powder is 1:200 to 1:20, and the mass ratio of the solvent to the coarse solid electrolyte powder is 1:1 to 20:1;
[0017] wet-grinding the mixed slurry to prepare a first slurry;
[0018] Transferring the first slurry into a closed container for a first heat treatment to obtain a second slurry;
[0019] Drying the second slurry to obtain a dry material;
[0020] The dry material is crushed to prepare the solid electrolyte powder.
[0021] In the present application, in the doped derivatives of NASICON-type phosphate solid electrolytes, the doped elements are selected from at least one of B, Si, Co, and Ni; in the doped derivatives of garnet-type lithium lanthanum zirconium oxide solid electrolytes, the doped elements are selected from at least one of W, Ta, Te, and Nb; in the doped derivatives of perovskite-type lithium lanthanum titanium oxide solid electrolytes, the doped elements are selected from at least one of Mg, Sr, W, and Nb. The solid electrolyte coarse powder can be prepared by any method in the prior art, and the particle size of the solid electrolyte coarse powder is usually in the micron level. The surfactant can be a soluble solid or a liquid, which includes a functional group. When the solid electrolyte coarse powder is dispersed in a solvent, the surfactant surrounds the outside of the solid electrolyte coarse powder, so that the interface between the solid electrolyte coarse powder and the solvent is changed to the contact interface between the functional group of the surfactant and the solvent, thereby promoting the solid electrolyte coarse powder to be uniformly and stably dispersed in the solvent. Specifically, the solid electrolyte coarse powder, the surfactant, and the solvent can be added to a stirring tank, respectively, and mixed by stirring until uniformly stirred to prepare a mixed slurry. The specific stirring process, such as stirring speed, temperature, etc., is not specifically limited in this application, so as to mix the slurry evenly. The mass ratio of surfactant to solid electrolyte coarse powder is 1:200 to 1:20, for example, it can be 1:200, 1:180, 1:160, 1:140, 1:120, 1:100, 1:80, 1:60, 1:45, 1:20, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable. Further preferably, the mass ratio of surfactant to solid electrolyte coarse powder is 1:100 to 1:45. The mass ratio of solvent to solid electrolyte coarse powder is 1:1 to 20:1, for example, it can be 1:1, 2:1, 3:1, 4:1, 6:1, 8:1, 9:1, 12:1, 15:1, 20:1, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable. More preferably, the mass ratio of the solvent to the coarse solid electrolyte powder is 9:1 to 4:1.
[0022] The mixed slurry is wet-milled to grind the coarse solid electrolyte powder in the mixed slurry into solid electrolyte particles with uniform nanometer particle size. The surfactant is wrapped around the periphery of the nano solid electrolyte particles, which can effectively prevent the nano solid electrolyte particles from agglomerating and coarsening, so as to obtain a first slurry containing uniformly dispersed nano solid electrolyte particles.
[0023] By performing the first heat treatment on the first slurry, the chemical reaction between the surfactant and the original hydrophilic groups on the surface of the solid electrolyte particles can be promoted, thereby forming hydrophobic surface functional groups on the surface of the solid electrolyte particles, so as to avoid the problem of nanoparticle agglomeration of the solid electrolyte powder in the subsequent drying process.
[0024] The second slurry is dried to dry the solvent in the second slurry, so as to obtain a soft and agglomerated dry material similar to flour. Specifically, a vacuum drying oven can be used for vacuum drying. Those skilled in the art can adjust the specific temperature and drying time of the vacuum drying oven according to the solvent content and type in the second slurry. The present application does not make any specific limitation on this. It is sufficient to dry the second slurry.
[0025] The dry material is crushed to obtain a solid electrolyte powder containing solid electrolyte particles with a particle size of nanometer level. The particle size of the solid electrolyte particles is D 50 Less than or equal to 500nm, D 90 / D 50 ≤3.0, the specific surface area of solid electrolyte particles is greater than 20m 2 / g. Specifically, the dry material can be pulverized by airflow pulverization, which is suitable for industrial production and has high production efficiency. The specific process parameters of airflow pulverization are not specifically limited in this application, and those skilled in the art can set them according to the requirements such as the particle size to be obtained.
[0026] The solid electrolyte powder prepared by the method of the present application can be stably stored, wherein the solid electrolyte particles are nano-sized, and have uniform particle size, good dispersibility, and low degree of agglomeration. When used, the solid electrolyte powder can be directly coated on the surface of the electrode material by a dry method without drying a large amount of solvent. The process is simple, and the production cost of the solid electrolyte-coated electrode material is greatly reduced.
[0027] Further, the surfactant is at least one of sodium dodecylbenzene sulfonate, polyvinyl pyrrolidone, polyethylene glycol, stearic acid, silane coupling agent, and fluorine-containing nonionic surfactant. When the surfactant is at least two of them, it can be a combination of any two or more of sodium dodecylbenzene sulfonate, polyvinyl pyrrolidone, polyethylene glycol, stearic acid, silane coupling agent, and fluorine-containing nonionic surfactant. Fluorine-containing nonionic surfactants include water-soluble fluorine-containing polyoxyethylene ether nonionic surfactants.
[0028] Further, the solvent is at least one of deionized water, ethanol, isopropanol, N-methylpyrrolidone (NMP), toluene, acetone, n-butanol and N,N-dimethylformamide (DMF). When the solvent is two or more of them, it can be a combination of any two or more of deionized water, ethanol, isopropanol, N-methylpyrrolidone (NMP), toluene, acetone, n-butanol and N,N-dimethylformamide (DMF). The type of solvent needs to match the type of surfactant to be miscible. For example, when the surfactant is at least one of sodium dodecylbenzene sulfonate and silane coupling agent, the solvent is preferably deionized water.
[0029] Furthermore, the wet grinding treatment is performed using a ball mill. Specifically, zirconium beads can be added to the ball mill for ball milling. Those skilled in the art can select the diameter and quantity of zirconium beads according to the ball milling method in the prior art, which will not be described in detail here.
[0030] Preferably, the rotation speed of the wet grinding treatment is 1000 rpm to 2200 rpm, such as 1000 rpm, 1200 rpm, 1500 rpm, 1800 rpm, 2000 rpm, 2200 rpm, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. More preferably, the rotation speed of the wet grinding treatment is 1500 rpm to 2000 rpm.
[0031] Preferably, the wet grinding treatment time is 1 h to 5 h, such as 1 h, 2 h, 3 h, 4 h, 5 h, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. More preferably, the wet grinding treatment time is 1 h to 3 h.
[0032] Under the above rotation speed and treatment time of wet grinding treatment, the solid electrolyte coarse powder in the mixed slurry can be ground into nano-scale solid electrolyte particles to obtain the first slurry containing uniformly dispersed nano solid electrolyte particles.
[0033] Further, the temperature of the first heat treatment is 50°C to 200°C, for example, 50°C, 75°C, 100°C, 125°C, 150°C, 175°C, 200°C, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. More preferably, the temperature of the first heat treatment is 100°C to 150°C.
[0034] Preferably, the treatment time of the first heat treatment is 0.5h to 24h, such as 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. More preferably, the treatment time of the first heat treatment is 4 to 12h.
[0035] At the temperature and treatment time of the first heat treatment, the chemical reaction between the surfactant and the original hydrophilic groups on the surface of the solid electrolyte particles can be promoted, thereby forming hydrophobic surface functional groups on the surface of the solid electrolyte particles, so as to avoid the problem of nanoparticle agglomeration of the solid electrolyte powder in the subsequent drying process.
[0036] Preferably, the sealed container is a high pressure resistant sealed container, such as a hydrothermal reactor, etc.;
[0037] Preferably, the first heat treatment is performed in a high-temperature forced air oven.
[0038] In a third aspect, the present application provides a solid electrolyte-coated electrode material, comprising an electrode material and the above-mentioned solid electrolyte powder, wherein the solid electrolyte powder is coated on the outside of the electrode material.
[0039] The solid electrolyte coated electrode material provided in the present application is coated with the aforementioned solid electrolyte powder on the outside of the electrode material. The solid electrolyte coated electrode material can be prepared by directly dry mixing the solid electrolyte powder with the electrode material, and the coating is uniform, which is easy to industrialize and has low production cost.
[0040] In a fourth aspect, the present application provides an application method of the above-mentioned solid electrolyte powder, the application method comprising the following steps:
[0041] The solid electrolyte powder and the electrode material are mixed to obtain a mixed material, wherein the mass ratio of the solid electrolyte powder to the electrode material is 1:200 to 1:50;
[0042] The mixed material is subjected to a second heat treatment to obtain an electrode material coated with a solid electrolyte.
[0043] In the present application, the mass ratio of the solid electrolyte powder to the electrode material is 1:200 to 1:50, for example, it can be 1:200, 1:180, 1:160, 1:140, 1:120, 1:100, 1:80, 1:70, 1:60, 1:50, etc., but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable. Preferably, the mass ratio of the solid electrolyte powder to the electrode material is 1:200 to 1:100. The solid electrolyte powder of the present application is composed of nanometer-scale solid electrolyte particles with uniform particle size, good dispersibility, and low degree of agglomeration, wherein the particle size D of the solid electrolyte particles is 50 Less than or equal to 500nm, the D 90 / D 50 ≤3.0, the specific surface area of solid electrolyte particles is less than 20m 2 / g, the solid electrolyte powder is directly coated on the surface of the electrode material by a dry method, without the need to dry a large amount of solvent, the process is simple, and the production cost of the solid electrolyte coated electrode material is greatly reduced.
[0044] Further, the temperature of the second heat treatment is 200°C to 800°C, for example, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. More preferably, the temperature of the second heat treatment is 300°C to 500°C.
[0045] Preferably, the treatment time of the second heat treatment is 0.5h to 12h, such as 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 12h, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. More preferably, the treatment time of the second heat treatment is 1h to 3h.
[0046] Under the temperature and treatment time of the above-mentioned second heat treatment, the electrode material can undergo a slight chemical reaction with the solid electrolyte powder attached to the surface, and the metal elements in the solid electrolyte powder can diffuse into the surface layer of the electrode material to form a slight doping, thereby stabilizing the surface layer of the electrode material. At the same time, the solid electrolyte powder remaining on the surface can act as a lithium ion conductor, thereby improving the lithium ion diffusion kinetics on the surface of the electrode material during the charging and discharging process.
[0047] Furthermore, the electrode material is selected from at least one of lithium cobalt oxide, NCM ternary material, lithium iron phosphate or lithium iron manganese phosphate material.
[0048] Implementing the embodiments of the present application will have the following beneficial effects:
[0049] The present application directly prepares solid electrolyte powders, wherein the solid electrolyte particles contained therein are nano-sized, and have uniform particle size, good dispersibility, and low degree of agglomeration. When used, the solid electrolyte powders can be directly coated on the surface of the electrode material by a dry method, without the need to dry a large amount of solvent. The process is simple, and the production cost of the solid electrolyte-coated electrode material is greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0051] in:
[0052] Figure 1 This is the particle size distribution spectrum of the solid electrolyte powder prepared in Example 1.
[0053] Figure 2This is a scanning electron microscope image of the solid electrolyte powder prepared in Example 1.
[0054] Figure 3 This is the particle size distribution spectrum of the solid electrolyte powder prepared in Example 7.
[0055] Figure 4 This is the particle size distribution spectrum of the solid electrolyte powder prepared in Comparative Example 1.
[0056] Figure 5 This is the particle size distribution spectrum of the solid electrolyte powder prepared in Comparative Example 2. DETAILED DESCRIPTION
[0057] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of the present application; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit the present application; the terms "including" and "having" and any variations thereof in the specification and claims of the present application and the above-mentioned drawings are intended to cover non-exclusive inclusions. The terms "first", "second", etc. in the specification and claims of the present application or the above-mentioned drawings are used to distinguish different objects, not to describe a specific order.
[0058] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0059] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings.
[0060] In the examples of the present application, the homemade materials are all prepared by the preparation methods disclosed in the prior art. Those skilled in the art can prepare them by any feasible preparation method in the prior art. The synthesis process of the homemade materials will not be described in detail in the examples of the present application.
[0061] Example 1
[0062] Weigh 200g of lithium aluminum titanium phosphate (Li 1.3 Al 0.3 Ti 1.7(PO4)3, homemade) solid electrolyte coarse powder, 2g polyvinyl pyrrolidone (PVP, Shanghai Aladdin Biochemical Technology Co., Ltd.), and 2000g deionized water were added into the stirring tank of a horizontal sand mill, respectively, and stirred at 1000 rpm for 30 minutes to prepare a mixed slurry;
[0063] The mixed slurry was ball-milled using a horizontal sand mill at a ball-milling speed of 2200 rpm for 3 hours to prepare a first slurry;
[0064] The first slurry after ball milling was transferred to a hydrothermal kettle and allowed to stand at 120° C. for 12 h to obtain a second slurry;
[0065] The second slurry after the static treatment was vacuum dried in a vacuum drying oven at 100° C. for 12 hours to obtain a dry powder;
[0066] The dry powder was subjected to air flow pulverization, and the pulverizing air flow pressure was set to 0.8 MPa, the screw feeding frequency was 10 Hz, the induced draft frequency was 45 Hz, and the classification frequency was 90 Hz to obtain a solid electrolyte powder, in which the solid electrolyte particles were of nanometer particle size level, and the particle size was uniform and easy to disperse.
[0067] SEM images of solid electrolyte powders Figure 1 As shown, from Figure 1 It can be seen that the particle size of the solid electrolyte particles is uniform and there is no obvious agglomeration. The particle size distribution diagram of the solid electrolyte powder is shown in Figure 2 As shown, D 10 =150nm, D 50 =239nm, D 90 =439nm, D 90 / D 50 =1.84, D 90 / D 10 =2.93. The specific surface area of the solid electrolyte particles is 42m 2 / g. The tap density of the solid electrolyte powder is 0.21g / cm 3 .
[0068] Example 2
[0069] Weigh 200g of lithium aluminum titanium phosphate (Li 1.3 Al 0.3 Ti 1.7 (PO4)3, homemade) solid electrolyte coarse powder, 1g polyvinylpyrrolidone (PVP, Shanghai Aladdin Biochemical Technology Co., Ltd.), 4000g deionized water, and the rest are the same as in Example 1.
[0070] Example 3
[0071] Weigh 200g of lithium aluminum titanium phosphate (Li 1.3 Al 0.3 Ti 1.7 (PO4)3, homemade) solid electrolyte coarse powder, 10g polyvinylpyrrolidone (PVP, Shanghai Aladdin Biochemical Technology Co., Ltd.), 200g deionized water, and the rest are the same as in Example 1.
[0072] Example 4
[0073] The first slurry after ball milling was transferred to a hydrothermal kettle and allowed to stand at 200° C. for 0.5 h. The rest was the same as in Example 1.
[0074] Example 5
[0075] The ball-milled slurry was transferred to a hydrothermal kettle and allowed to stand at 50° C. for 24 h. The rest was the same as in Example 1.
[0076] Example 6
[0077] The polyvinyl pyrrolidone was replaced by polyethylene glycol 400, and the deionized water was replaced by ethanol. The rest was the same as in Example 1.
[0078] Example 7
[0079] Replace lithium aluminum titanium phosphate with tungsten-doped lithium lanthanum zirconium oxide (Li 6.28 W 0.12 La3Zr2O 12 , homemade), polyvinyl pyrrolidone was replaced with silane coupling agent KH550 (γ-aminopropyltriethoxysilane C9H 23 NO3Si, Shanghai Aladdin Biochemical Technology Co., Ltd.), and the rest is the same as Example 1. The particle size distribution of the solid electrolyte powder is shown in Figure 3 shown.
[0080] Example 8
[0081] Replace lithium aluminum titanium phosphate with lithium lanthanum titanium oxide (Li 0.48 La 0.505 TiO3, homemade), polyvinyl pyrrolidone was replaced by a fluorinated nonionic surfactant (FS-3100, Shanghai Huifei Chemical Co., Ltd.), and the rest was the same as in Example 1.
[0082] Example 9
[0083] The time for ball milling the mixed slurry in the horizontal sand mill in Example 1 was shortened to 1 hour, and the rest was the same as in Example 1.
[0084] Example 10
[0085] The rotation speed of the horizontal sand mill for ball milling the mixed slurry in Example 1 was reduced from 2200 rpm to 1000 rpm, and the ball milling time was extended from 3 hours to 5 hours. The rest was the same as in Example 1.
[0086] Embodiment 11
[0087] Weigh 50g of lithium aluminum titanium phosphate (Li 1.3 Al 0.3 Ti 1.7 (PO4)3, homemade) solid electrolyte coarse powder, 2.5g polyvinyl pyrrolidone (PVP, Shanghai Aladdin Biochemical Technology Co., Ltd.), 950g deionized water, the mixed slurry was ball-milled in a horizontal sand mill for 5 hours to prepare a first slurry; the treatment conditions of the first slurry in the hydrothermal autoclave were standing at 180°C for 12h, and the rest were the same as Example 1.
[0088] Comparative Example 1
[0089] 200 g of lithium aluminum titanium phosphate solid electrolyte coarse powder and 2000 g of deionized water were added into a stirring tank of a horizontal sand mill, and stirred at 1000 rpm for 30 minutes to prepare a mixed slurry;
[0090] The mixed slurry was ball-milled using a horizontal sand mill at a ball-milling speed of 2200 rpm for 3 hours to prepare a first slurry;
[0091] The first slurry after ball milling was transferred to a hydrothermal kettle and allowed to stand at 120° C. for 12 h to obtain a second slurry;
[0092] Then, the second slurry was vacuum dried in a vacuum drying oven at 100° C. for 12 hours to obtain a dry powder;
[0093] The dry powder is subjected to air flow pulverization to obtain solid electrolyte powder.
[0094] The particle size distribution of solid electrolyte powder is as follows Figure 4 As shown, where D 10 =147nm, D 50 =889nm, D 90 =4936nm, D 90 / D 50 =5.55, D 90 / D 10 =33.58. The specific surface area of the solid electrolyte particles is 12m 2 / g. The tap density of the solid electrolyte powder is 0.87g / cm 3 .
[0095] Comparative Example 2
[0096] Weigh 200 g of lithium aluminum titanium phosphate, 2 g of polyvinyl pyrrolidone, and 2000 g of deionized water, add them into a stirring tank of a horizontal sand mill, and stir them at 1000 rpm for 30 minutes to prepare a mixed slurry;
[0097] The mixed slurry was ball-milled using a horizontal sand mill at a ball-milling speed of 2200 rpm for 3 hours to prepare a first slurry;
[0098] The first slurry after ball milling was vacuum dried in a vacuum drying oven at 100° C. for 12 hours to obtain a dry powder;
[0099] The dry powder is subjected to air flow pulverization to obtain solid electrolyte powder.
[0100] The particle size distribution of solid electrolyte powder is shown in Figure 5 As shown, D 10 =139nm, D 50 =281nm, D 90 =2922nm, D 90 / D 50 =10.40, D 90 / D 10 =21.02. The specific surface area of the solid electrolyte particles is 28m 2 / g. The tap density of the solid electrolyte powder is 0.42g / cm 3 .
[0101] The test results of the above-mentioned Examples 1 to 11 and Comparative Examples 1 to 2 can be specifically seen in the following table:
[0102]
[0103] From the comparison between Example 1 and Comparative Examples 1 and 2, it can be seen that the solid electrolyte powder prepared by Example 1 has a small particle size and concentrated distribution, and the particles are not agglomerated. Without using a surfactant or without undergoing the first heat treatment process, the solid electrolyte powder obtained is obviously agglomerated, the particles are large and unevenly distributed, and the fluidity of the powder is very poor. In Examples 1 to 11, by increasing or decreasing the amount of surfactant, increasing or decreasing the temperature and time of the first heat treatment, changing the type of surfactant and the type of solvent, etc., the final particle size of the powder will be affected to a certain extent, but the solid electrolyte powder obtained generally still maintains the characteristics of uniform particle size and good dispersibility.
[0104] Example 12
[0105] 0.1 g of the solid electrolyte powder obtained in Example 1 and 10 g of the ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2(D 50The particle size is 3.77 μm, Dongguan Kelude Experimental Equipment Technology Co., Ltd.) was added into a ball mill and mixed with a planetary ball mill at a speed of 300 rpm for 1 hour to obtain a mixed material.
[0106] The mixed material is transferred to a tube furnace, oxygen is passed through, and heat-treated at 400°C for 3 hours to obtain a solid electrolyte-coated electrode material;
[0107] The solid electrolyte coated electrode material obtained in Example 12 was used as the positive electrode material, and was mixed in a ratio of positive electrode material: acetylene black: PVDF = 90:5:5 with NMP as solvent. The mixed slurry was evenly coated on the aluminum current collector using an experimental coating machine. The electrode sheet after drying and rolling was cut into a 14 mm diameter disc using a die cutter to obtain the required single-sided coated positive electrode sheet. The surface density of the positive electrode sheet is 12 mg / cm 2 , compacted density is 3.2mg / cm 3 The negative electrode uses metallic lithium with a thickness of 0.45mm. It is assembled into a lithium-ion button cell in a glove box protected by an inert atmosphere (water content ≤5ppm). The charge and discharge performance test is performed at 0.5C. The first cycle charge and discharge specific capacity and the first cycle coulomb efficiency are calculated. The test conditions are room temperature and the limiting voltage is 2.8V-4.3V.
[0108] Example 13
[0109] 0.05 g of the solid electrolyte powder obtained in Example 1 and 10 g of the ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2 was added into the ball mill, and the rest was the same as in Example 12.
[0110] Embodiment 14
[0111] 0.5 g of the solid electrolyte powder obtained in Example 1 and 10 g of the ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2 was added into the ball mill, and the rest was the same as in Example 12.
[0112] Embodiment 15
[0113] The mixed material was calcined at 800°C for 0.5 hour, and the rest was the same as in Example 12.
[0114] Example 16
[0115] The mixed material was heat treated at 200°C for 12 hours, and the rest was the same as Example 12.
[0116] Comparative Example 3
[0117] According to the first three steps of Example 1, a second slurry of lithium aluminum titanium phosphate was obtained, and 1 g of the second slurry and 10 g of the ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2 was added to the ball mill, and then 2 g of deionized water was added and mixed for 1 hour to obtain a blended slurry;
[0118] The blended slurry was vacuum dried in a vacuum box at 100° C. for 6 hours to obtain a dried mixture, and the obtained mixture was transferred to a tubular furnace, oxygen was passed through, and heat treated at 400° C. for 3 hours to obtain a solid electrolyte-coated electrode material.
[0119] The positive electrode was prepared using the solid electrolyte-coated electrode material obtained in Comparative Example 3, and a lithium-ion battery was further assembled. The charge and discharge performance test was performed at 0.5C at room temperature. The limiting voltage at room temperature was 2.8V-4.3V. The specific steps were the same as those in Example 12.
[0120] Comparative Example 4
[0121] The deionized water in Example 1 and Comparative Example 3 was replaced with ethanol, and an ethanol slurry of lithium aluminum titanium phosphate (LATP) was obtained according to the first three steps of Example 1. The remaining steps were the same as those in Comparative Example 3.
[0122] The test results of the above-mentioned Examples 12 to 16 and Comparative Examples 3 to 4 can be specifically seen in the following table:
[0123]
[0124] It can be seen from Examples 12 to 16 that by changing the coating amount and the heat treatment process, the performance of the electrode material coated with the solid electrolyte will change, all of which are within a relatively optimal range and meet the requirements for commercial use.
[0125] From the comparison between Example 12 and Comparative Example 3, it can be seen that the electrode material obtained by directly dry coating the solid electrolyte powder prepared by the present application has a charge specific capacity and coulombic efficiency far superior to the electrode material obtained by wet coating with aqueous solid electrolyte slurry. The solid electrolyte powder prepared by the present application is nanometer-level, has good dispersibility, and uniform particle size. It can be well coated on the outside of the electrode material by dry coating, and the coated electrode material has good electrochemical performance. Comparative Example 3 uses aqueous LATP slurry for coating. Due to the ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2 is sensitive to water, so the coating effect is very poor.
[0126] From the comparison between Example 12 and Comparative Example 4, it can be seen that the electrode material obtained by directly dry-coating the solid electrolyte powder prepared by the present application has a charge specific capacity and coulombic efficiency close to that of the electrode material coated with lithium aluminum titanium phosphate (LATP) ethanol slurry. However, when the solid electrolyte powder of the present application is directly coated, there is no need to vacuum dry the ethanol during the coating process, the coating process is simple and easy, the production cost is low, and the safety is greatly improved.
[0127] Obviously, the embodiments described above are only some embodiments of the present application, rather than all embodiments. The preferred embodiments of the present application are given in the accompanying drawings, but they do not limit the patent scope of the present application. The present application can be implemented in many different forms. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive. Although the present application is described in detail with reference to the aforementioned embodiments, for those skilled in the art, it is still possible to modify the technical solutions recorded in the aforementioned specific implementation methods, or to perform equivalent replacement of some of the technical features therein. Any equivalent structure made using the contents of the specification and drawings of this application, directly or indirectly used in other related technical fields, is similarly within the scope of patent protection of this application.
Claims
1. A solid electrolyte powder, characterized in that: The solid electrolyte powder comprises solid electrolyte particles, the material of the solid electrolyte powder comprises at least one of NASICON-type phosphate solid electrolyte and its doped derivatives, garnet-type lithium lanthanum zirconium oxide solid electrolyte and its doped derivatives, and perovskite-type lithium lanthanum titanium oxide solid electrolyte and its doped derivatives, and the particle size D of the solid electrolyte particles is 50 Less than or equal to 500nm, D 90 / D 50 ≤3.0, the specific surface area of the solid electrolyte particles is greater than 20m 2 / g.
2. The solid electrolyte powder according to claim 1, characterized in that The particle size D of the solid electrolyte particles 50 is 20nm to 500nm, and the D 90 / D 10 ≤5, the specific surface area of the solid electrolyte particles is 22m 2 / g~100m 2 / g.
3. The solid electrolyte powder according to claim 1, characterized in that The particle size D of the solid electrolyte particles 50 The solid electrolyte particles have a diameter of 1.5 ≤ D 90 / D 50 ≤3.0, 2.5≤D of the solid electrolyte particles 90 / D 10 ≤5, the specific surface area of the solid electrolyte particles is 22m 2 / g~60m 2 / g.
4. The solid electrolyte powder according to claim 1, characterized in that The tap density of the solid electrolyte powder is 0.05 g / cm 3 ~0.4g / cm 3 Preferably, the tap density of the solid electrolyte powder is 0.1 g / cm 3 ~0.4g / cm 3 .
5. A method for preparing a solid electrolyte powder as claimed in claim 1, characterized in that: The method comprises the following steps: Mixing a solid electrolyte coarse powder, a surfactant and a solvent to prepare a mixed slurry, wherein the material of the solid electrolyte coarse powder includes at least one of a NASICON-type phosphate solid electrolyte and a doped derivative thereof, a garnet-type lithium lanthanum zirconium oxide solid electrolyte and a doped derivative thereof, and a perovskite-type lithium lanthanum titanium oxide solid electrolyte and a doped derivative thereof, the mass ratio of the surfactant to the solid electrolyte coarse powder is 1:200 to 1:20, and the mass ratio of the solvent to the solid electrolyte coarse powder is 1:1 to 20:1; wet-grinding the mixed slurry to prepare a first slurry; Transferring the first slurry into a closed container for a first heat treatment to obtain a second slurry; Drying the second slurry to obtain a dry material; The dry material is crushed to prepare the solid electrolyte powder.
6. The method for preparing a solid electrolyte powder according to claim 5, characterized in that: The surfactant is at least one of sodium dodecylbenzene sulfonate, polyvinyl pyrrolidone, polyethylene glycol, stearic acid, a silane coupling agent, and a fluorine-containing nonionic surfactant.
7. The method for preparing a solid electrolyte powder according to claim 5, characterized in that: The solvent is at least one of deionized water, ethanol, isopropanol, N-methylpyrrolidone, toluene, acetone, n-butanol and N,N-dimethylformamide.
8. The method for preparing a solid electrolyte powder according to claim 5, characterized in that: The rotation speed of the wet grinding treatment is 1000 rpm to 2200 rpm, and the treatment time of the wet grinding treatment is 1 h to 5 h.
9. The method for preparing a solid electrolyte powder according to claim 5, characterized in that: The temperature of the first heat treatment is 50° C. to 200° C., and the treatment time of the first heat treatment is 0.5 h to 24 h.
10. A solid electrolyte coated electrode material, characterized in that: The invention comprises an electrode material and the solid electrolyte powder according to any one of claims 1 to 4, wherein the solid electrolyte powder is coated on the outside of the electrode material.
11. A method for using the solid electrolyte powder according to any one of claims 1 to 4, characterized in that: The application method comprises the following steps: The solid electrolyte powder and the electrode material are mixed to obtain a mixed material, wherein the mass ratio of the solid electrolyte powder to the electrode material is 1:200 to 1:50; The mixed material is subjected to a second heat treatment to obtain an electrode material coated with a solid electrolyte.
12. The method for applying the solid electrolyte powder according to claim 11, characterized in that: The temperature of the second heat treatment is 200°C to 800°C; Preferably, the treatment time of the second heat treatment is 0.5h to 12h.
13. The method for applying the solid electrolyte powder according to claim 11, characterized in that: The electrode material is selected from at least one of lithium cobalt oxide, NCM ternary material, lithium iron phosphate or lithium iron manganese phosphate material.
Citation Information
Cited By
Oxide solid electrolyte and preparation method and application thereof
CN121662937A
Oxide solid electrolyte, method for preparing same, and use thereof
CN121662937B